Identification and Quantification of Glucosinolates in Kimchi by Liquid Chromatography-Electrospray Tandem Mass Spectrometry - Ho Jin Kim; Mi Jin Lee; Min Hee Jeong; Jang Eok Kim (International Journal of Analytical Chemistry)
A novel and simple method for detecting five glucosinolates (glucoalyssin, gluconapin, glucobrassicanapin, glucobrassicin, and 4-methoxyglucobrassicin) in kimchi was developed using liquid chromatography-electrospray tandem mass spectrometry (LC-MS/MS). The chromatographic peaks of the five glucosinolates were successfully identified by comparing their retention times, mass spectra. The mobile phase was composed of A (acetonitrile) and B (water). As for glucosinolate, the relative quantities were found through sinigrin, and five different compounds that have not been previously discovered in kimchi were observed. Monitoring was carried out on the glucosinolate in 20 kimchis distributed in markets, and this study examined the various quality and quantity compositions of the five components. The glucoalyssin content ranged from 0.00 to 7.07 μmol/g of day weight (DW), with an average content of 0.86 μmol/g of DW, whereas the gluconapin content ranged from 0.00 to 5.85 μmol/g of DW, with an average of 1.17 μmol/g of DW. The content of glucobrassicanapin varied between 0.00 and 11.87 μmol/g of DW (average = 3.03 μmol/g of DW), whereas that of glucobrassicin varied between 0.00 and 0.42 μmol/g of DW (average = 0.06 μmol/g of DW). The 4-methoxyglucobrassicin content ranged from 0.12 to 9.36 μmol/g of DW (average = 3.52 μmol/g of DW). A comparison of the contents revealed that, in most cases, the content of 4-methoxyglucobrassicin was the highest.